Molecular identification of Ixodid ticks of mithun from Nagaland - KCHAMUAH, J; LAMA, S; DUTTA, P R; RAINA, O K; KHAN, M H (The Indian Journal of Animal Sciences, 2016)
An animal health check-up and treatment camp during the year 2015 for the free ranging mithun (Bos frontalis) organized at Khonoma and Jotsoma villages of Kohima district, Nagaland showed Ixodid tick infestation on these animals, with the ticks attached to the dewlap and inner aspects of the thighs. Based on their morphological features, the ticks were identified to belong to the genus Ixodes. However, identification of these ticks to Ixodes ovatus and I. acutitarsus was made by the sequence analysis of the internal transcribed spacer-2 region of these ticks. The present study showed both I. ovatus and I. acutitatarsus are prevalent on the mithun in this area and is the first report on the occurrence of I. ovatus on the mithun.